GRB host galaxies with strong H2 absorption: CO-dark molecular gas at the peak of cosmic star formation. Issue 1 (29th July 2021) - Heintz, K E; Björnsson, G; Neeleman, M; Christensen, L; Fynbo, J P U; Jakobsson, P; Krogager, J-K; Laskar, T; Ledoux, C; Magdis, G; Møller, P; Noterdaeme, P; et al.
ABSTRACT: We present a pilot search of CO emission in three H2 -absorbing, long-duration gamma-ray burst (GRB) host galaxies at z ∼ 2–3. We used the Atacama Large Millimeter/submillimeter Array (ALMA) to target the CO(3 − 2) emission line and report non-detections for all three hosts. These are used to place limits on the host molecular gas masses, assuming a metallicity-dependent CO-to-H2 conversion factor (αCO ). We find, M_mol 3.5× 10^10 M_ (GRB 080607), M_mol 4.7× 10^11 M_ (GRB 120815A), and M_mol 8.9× 10^11 M_ (GRB 181020A). The high limits on the molecular gas mass for the latter two cases are a consequence of their low stellar masses M ⋆ (M_10^8 M_ ) and low gas-phase metallicities (Z0.03 Z_ ). The limit on the M mol / M ⋆ ratio derived for GRB 080607, however, is consistent with the average population of star-forming galaxies at similar redshifts and stellar masses. We discuss the broader implications for a metallicity-dependent CO-to-H2 conversion factor and demonstrate that the canonical Galactic αCO will severely underestimate the actual molecular gas mass for all galaxies at z > 1 with M_10^10 M_ . To better quantify this we develop a simple approach to estimate the relevant αCO factor based only on the redshift and stellar mass of individual galaxies. The elevated conversion factors will make these galaxies appear CO-'dark' and difficult to detect in emission, as is the case for the majority of GRB hosts. GRB spectroscopy thus offers a complementary approach to identify low-metallicity, star-forming galaxies with abundant molecular gas reservoirs at high redshifts that are otherwise missed by current ALMA surveys.